2020
DOI: 10.1021/acs.orglett.0c03395
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Nickel-Catalyzed Hydroarylation of Styrenes

Abstract: The mechanism of nickel-catalyzed hydroarylation of styrenes has been explored with density functional theory. Instead of the stepwise pathway via a Ni­(II)–H species, computational results unveil that the concerted RO–H oxidative addition/olefin insertion takes place kinetically favorable to generate the alkylnickel­(II) species, which further undergoes transmetalation and reductive elimination to yield the hydroarylated product. The origins of regio- and stereoselectivity were revealed via analyzing the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…In these reports, it is often suggested that the oxidative addition of an alcohol to the nickel(0) center to generate a nickel hydride species is a key step in the formation of the alkyl nickel­(II) species (path A). However, computational studies have suggested that the oxidative protometallation of alkenes by the nickel(0) complex and a hydroxy group would be a reasonable mechanism for the hydroarylation (path B). , Thus, the mechanisms underlying the nickel-catalyzed alkene isomerization and hydroarylation remain partially elusive.…”
mentioning
confidence: 99%
“…In these reports, it is often suggested that the oxidative addition of an alcohol to the nickel(0) center to generate a nickel hydride species is a key step in the formation of the alkyl nickel­(II) species (path A). However, computational studies have suggested that the oxidative protometallation of alkenes by the nickel(0) complex and a hydroxy group would be a reasonable mechanism for the hydroarylation (path B). , Thus, the mechanisms underlying the nickel-catalyzed alkene isomerization and hydroarylation remain partially elusive.…”
mentioning
confidence: 99%
“…The computational results described the actual origins of the stereo and regioselectivity (Scheme 6). 25 This approach demonstrated that the mechanism could have proceeded via the generation of the kinetically-favored alkylnickel(II) intermediate directly from the concerted R-OH oxidative addition/olefin migratory insertion step, followed by transmetallation and reductive elimination of C and D to generate the desired corresponding product 11. The branching selectivity was caused by a combination of steric repulsions between the substrate and the phenyl group's electronic effect on the charge distribution over the C α vC β bond.…”
Section: Hydroarylation Reactions Of Boronic Acid Derivativesmentioning
confidence: 99%
“…7e, 14 To date, progress on asymmetric catalysis has focused on enantioselective hydroarylation. [20][21][22][23][24][25] In 2019, Ni-catalyzed enantioselective hydroarylation of styrenes with arylboronic acids was demonstrated by Zhou et al 20 22 . Due to the low reactivity of hydronickelation, the alkene scope in this reaction is limited to β-unsubstituted styrenes.…”
Section: Asymmetric Catalysismentioning
confidence: 99%
“…7e, 14 To date, progress on asymmetric catalysis has focused on enantioselective hydroarylation. [20][21][22][23][24][25] In 2019, Ni-catalyzed enantioselective hydroarylation of styrenes with arylboronic acids was demonstrated by Zhou et al 20 using a spiro aminophosphine ligand L9 and by Mei's group 21 who used a bisoxazoline ligand L10 (Scheme 7). As shown in the originally proposed Ni(0)/Ni(II) catalytic cycle, enantioselective syn-hydrometallation of a ligated key intermediate RO-Ni(II)-H II into styrene 1 was suggested as path a, the enantiodetermining step.…”
Section: Asymmetric Catalysismentioning
confidence: 99%
See 1 more Smart Citation